APB Delegation's Visit to ORKIDS Headquarter - UiTM Shah Alam, Akademi Pengajian Bahasa (Academy of Language Studies, 2022)
On 22nd September 2022, Associate Professor Ts Dr Janudin Sardi, the Dean of Akademi Pengajian Bahasa with a delegation consisting of the Deputy Dean of Research, Community and Industry, Associate Professor Dr Nor Fazlin Mohd Ramli and other APB staff such as Dr Noor Ahnis Othman, Dr Syamimi Turiman, and Ms Hidayu Shafie visited the headquarter of ORKIDS. The meeting was conducted at the ORKIDS headquarter in Petaling Jaya, Selangor started at 10.30 am which ended at 12.00 noon. The aim of the visit was to further discuss future collaborative projects between APВ and ORKIDS.